Penatalaksanaan Abses Submandibula Sinistra Et Causa Gangren Radix Pada Pasien Hepatitis Di RSUD Sultan Fatah Demak - Syarifah Nova Amiza Zam; Fuad Fatkhurrohman -; Briliana Ikrimazahra; Dea Hardyana Putri; Nabela Intania Sekarini; Khairunnisa Pulungan (Cakradonya Dental Journal, 2024)
Submandibula abscess is a mixture of pus that collects in one area in a network, namely the submandibula area caused by bacterial infection, parasites, or other foreign bodies. The cause of submandibula infection generally originates from the mandibular first and second molar teeth from the spread of infection from the sublingual and submental spaces. Symptoms of a submandibula abscess are characterized by pain and swelling of the cheeks to the inner neck where infection occurs. Infection that occurs in the submandibula space originates from infection of the floor of the mouth, teeth, pharynx, and submandibula lymph nodes. A 49-year-old female patient came to the Sultan Fatah Hospital in Demak with clinical symptoms leading to a submandibula abscess, where there were complaints of swelling on the left cheek up to the neck, the remaining root teeth were often sore and loose, and shortness of breath. Radiological examination performed on the patient showed the impression of a left submandibula abscess. Laboratory tests obtained positive HbsAg indicating that the patient is infected with Hepatitis B. Hepatitis B is a disease that can worsen the condition of the immune system. Proper infection control and sterilization protocols must be followed to reduce the risk of infection.